PENGARUH PERLAKUAN ISTIMEWA, PERSEPSI INVESTASI HUBUNGAN DAN KOMUNIKASI INTERPERSONAL TERHADAP KUALITAS HUBUNGAN (STUDI KASUS PT. BPD DIY CABANG WATES) - Muhammad Tahwin; Septarani Prasiwi (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2016)
This study aims to analysis the preferential treatment, perceived relationship investment, and interpersonal communication as key factors influencing relationships quality. Analysis was performed on PT. BPD DIY Cabang Wates. A quantitative approach is employed. The data gathered using a survey method with questionnaire as an instrument of measurement. Scale which used to measure the answers of questionnaires questions using a likert scale with n=220 respondents as the samples. The data were analyzed using multiple regression analysis. Preferential treatment, perceived relationship investment, and interpersonal communication found have a positive significant impact on the relationship quality in PT. BPD DIY Cabang Wates. Keywords: preferential treatment, perceived relationship investment, interpersonal communication, and relationships quality